Monetary policy in the transition to a market economy: The case of Hungary - Thomas Apolte (Intereconomics, 1991)
In the centrally planned economies of Eastern Europe, monetary policy played a subordinate role, there were no capital-market institutions and the banking system was single-tier. All this has to be changed in the transition to a market economy. The example of Hungary, which abolished the traditional system of central planning as early as 1968, shows some of the pitfalls to be avoided.
Keywords: 330; System Transformation